RELEVANSI METODE MENGHAFAL NADZAMAN BAGI SANTRI UNTUK MEMAHAMI DAN MENGINGAT PELAJARAN - Moch Umar Faroq Al Farizi; Muhammad Husni (JURNAL ILMIAH RESEARCH STUDENT, 2026)
This study aims to analyze the relevance of the nadzaman memorization method as a learning strategy in Islamic boarding schools (pesantren) in enhancing students’ ability to understand and remember lesson materials. Nadzaman is a traditional method in the form of Arabic poetry or verses containing summaries of religious knowledge in easily memorizable stanzas. This research employs a qualitative approach with literature study and field observation methods in several pesantren. The findings indicate that the nadzaman method has high relevance in the context of pesantren learning due to several factors: (1) it facilitates the memorization process through rhyme and rhythm patterns, (2) enhances long-term memory retention, (3) integrates Arabic language learning with religious materials, and (4) preserves the classical Islamic scholarly tradition. This study concludes that the nadzaman method remains relevant as one of the learning methods in modern pesantren, although it needs to be integrated with contemporary learning methods for more optimal results.